Experimental Investigation on the Performance Analysis of a Constructed Hydro-Powered Coil Pump - HOSSAIN, Md. Alamgir; RAHMAN, Minhaj; FAHAD, Shariful Islam (Engineering Transactions, 2024)
A hydro-powered water pumping system is one of the most important systems for upland areas in terms of supplying water for irrigation and daily usage. This paper presents the development and performance analysis of a hydro-powered coil pump, a clean energy pump that discharges and lifts water to a certain height without using any external energy sources. In this work, a coil pump with a radius of 0.152 m, 12 blades, four inlets, and two different outlets with 1″ and 3/8″ delivery pipes have been used for analyzing the performance of the pump separately. An open channel has been constructed with a length of 1.152 m, a width of 0.3028 m, and a depth of 0.254 m, incorporating a rectangular and v-notch. From the analysis, it has been seen that the coil pump with a v-notch and a 1″ delivery pipe shows better results in terms of discharge, power acquired, and water velocity through the open channel than the coil pump with a 3/8″ delivery pipe. However, for pumping water at the maximum manometric height, a 3/8″ delivery pipe with a rectangular notch performs better than the v-notch.